Development of mini-CNC engraving machine / Ahmad Irfan Ahmad Fahmi - Ahmad Fahmi, Ahmad Irfan (2024)
Computer Numerical Control (CNC) machine is a machine that is pre-programmed with a computer software that dictates the movement of the cutting tool to fabricate a certain parts or prototype. For introduction, the machine that will be fabricated for this project is a small-scale CNC Engraving Machine. Its function is to cut, shape and create different parts and to also engrave on a material such as PCB. The purpose of making this machine is to help people fabricate the parts that they needed to use in small number. The main objective of this project is to design the mini-CNC engraving machine using SolidWorks and to fabricate the project as a proof of concept. The expected results for this project are to help people that make small or DIY project at home to fabricate the parts by themselves and they did not have to reach out to a company that specialize in CNC machining and pay large amount of money to fabricate the parts that they needed